Slavko Osterc und Karl Reiner im Briefwechsel - Matjaž Barbo (Musicologica Brunensia, 2019)
Several hundred different letters and postcards to the Osterc testify his extensive network of national and international contacts. In his entire legacy the correspondence with Reiner appears next to Hába as the most intense and rich. 39 letters have been received from Reiner's side, though the counter-correspondence unfortunately was not found. Reiner's letters to Osterc are full of various discussions about joint projects, the preparation of concerts, changes in interpreters, program etc. Their correspondence was most intense in the years 1933–1935.